(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The excess of ongoing lawsuits in the national judiciary (more than 100 million in 2017) is one of the factors behind the undue and longer-than-necessary maintenance of pre-trial detention in Brazil, impacting on public prison administration. This situation, coupled with the fact that Brazil does not comply with some of the rules set out in international treaties and conventions, including the obligation to immediately present people arrested in flagrante or by final decision to the competent judicial authority, led the CNJ to issue Resolution 213/2015, requiring custody hearings to be held throughout Brazil. This article looks at the historical evolution of the implementation of custody hearings in our country and discusses the constitutionality of requiring them through administrative regulations, without a formal law. It also aims to analyze the application of the principle of human dignity in the validation of such a resolution. In the end, it will assess whether the 24-hour deadline for any prisoner to be brought before a judge, provided for in the aforementioned resolution, can be demanded of the police authorities and the judiciary itself, without violating due process of law.